Postprandial lipemia as a cardiometabolic risk factor - Pirillo, A.; Norata, Giuseppe; Catapano, A. (Librapharm, 2014)
High levels of fasting circulating triglycerides (TG) represent an independent risk factor for cardiovascular disease. In western countries, however, people spend most time in postprandial conditions, with continuous fluctuation of lipemia due to increased levels of TG-rich lipoproteins (TRLs), including chylomicrons (CM), very low density lipoproteins (VLDL), and their remnants. Several factors contribute to postprandial lipid metabolism, including dietary, physiological, pathological and genetic factors. The presence of coronary heart disease, type 2 diabetes, insulin resistance and obesity is associated with higher postprandial TG levels compared with healthy conditions; this association is present also in subjects with normal fasting TG levels. Increasing evidence indicates that impaired metabolism of postprandial lipoproteins contributes to the pathogenesis of coronary artery disease, suggesting that lifestyle modifications as well as pharmacological approaches aimed at reducing postprandial TG levels might help to decrease the cardiovascular risk. © 2014 Informa UK Ltd.